Enraizamento e atividades enzimáticas associadas à forma de aplicação e doses de ácido indolbutírico em estacas de erva-mate - Tres, Laura (2019)
Mate herb seedlings are mainly produced from seeds, which results in plants with heterogeneous characteristics related to the phenotype, development and quality of the final product. The vegetative propagation by cutting is an alternative for the implantation of more uniform and productive herbs. The process of adventitious rooting is influenced by many factors, such as the cutting season, the natural presence of auxins or the treatment with phytoregulators and the action of oxidative enzymes. Indolbutyric acid (IBA) has been shown to be efficient in inducing rooting in mate herb, but there are evidences of phytotoxicity or stress effects. The objective of this research was to evaluate if the dose and the application form of IBA influence the rooting potential of cuttings of different mate herb genotypes, performing the cutting at different times and detecting what possible changes may occur in enzymatic activities during the process. The cutting was performed in the summer/fall (January to April) and in the spring (September to December) and conducted for 90 days. Four genotypes (G4, G15, G26 and G28), which were selected in a commercial place with mate herb cultivation, were assessed and the cuttings were treated with IBA applied as talc powder (2,000 and 4,000 mg kg-1) and in hydroalcoholic solution (2,000 and 4,000 mg L-1), compared to untreated cuttings. During the summer cutting season, changes in activity levels of peroxidase, polyphenoloxidase and IAA oxidase were also evaluated immediately after planting and repeated every seven days until 35 days after cutting. Cutting in summer/fall (January) is more indicated than in spring (September), with emphasis on the G4 and G26 genotypes, that presented higher percentage of rooted cuttings and development of the root system in both seasons. The forms and doses of IBA application did not change rooting rates, but the powder form may be an alternative to obtain better leaf retention and survival rates, even at higher doses, providing a better quality of the root system. The intense fall of leaves in the first three to four weeks, which is considered the most critical period, is related to the increased activity of peroxidase and polyphenoloxidase enzymes, but the degree of responses differs according to the genotype, IBA application form and, mainly, by the IBA dose. The peroxidase and polyphenoloxidase activities in relation to untreated cuttings, are not higher when subjected to IBA treatments. IAA oxidase activity peaks in the first seven days of cuttings, decreasing thereafter. In mate herb, it is not possible to establish, in the first 35 days, the relationship between enzyme activity and rooting results.